Simultaneous inferences for ordered exponential location parameters under unbalanced data and heteroscedasticity of scale parameters. Issue 4 (21st April 2017) - Gill, A. N.; Goyal, Anju; Maurya, Vishal
ABSTRACT: A test procedure for testing homogeneity of location parameters against simple ordered alternative is proposed for k(k ≥ 2) members of two parameter exponential distribution under unbalanced data and heteroscedasticity of the scale parameters. The relevant one-sided and two-sided simultaneous confidence intervals (SCIs) for all k(k − 1)/2 ordered pairwise differences of location parameters are also proposed. Simulation-based study revealed that the proposed procedure is better than the recently proposed procedure in terms of power, coverage probability, and average volume of SCIs. The implementation of proposed procedure is demonstrated through real life data.